(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Purse seine is an active and effective fishing gear that catches schooling pelagic fish. The principle of operation is to encircle a school of fish and narrow the movement area of the fish. Fishing activities are inseparable from the operational aspects of fishing gear operations. The operational aspects of operation organize the operation of a fishing activity, starting from planning to harvesting the catch according to the target and high economic value. This study aims to describe the operational aspects of operating using purse seine on the FV Laut Teberau 02. Data collection was done through observation and interviews. Data analysis using descriptive analysis The results showed that the operational aspects of fishing are activities conducted from the fishing base to the fishing ground and back to the fishing base. The technical aspects that support fishing operations using purse seine on KM. Laut Teberau 02 include vessels, fishing gear, Fish Aggregating Device (FAD’s), navigation tools, communication tools, personal safety tools, and work safety tools.